2011
DOI: 10.1161/circresaha.111.249433
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Transcriptome Complexity Through RNA Sequencing in Normal and Failing Murine Hearts

Abstract: Rationale Accurate and comprehensive de novo transcriptome profiling in heart is a central issue to better understand cardiac physiology and diseases. Although significant progress has been made in genome-wide profiling for quantitative changes in cardiac gene expression, current knowledge offers limited insights to the total complexity in cardiac transcriptome at individual exon level. Objective To develop more robust bioinformatic approaches to analyze high-throughput RNA sequencing (RNA-Seq) data, with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
162
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 193 publications
(170 citation statements)
references
References 23 publications
7
162
1
Order By: Relevance
“…72 In hypertrophied and failing mouse hearts, alternative splicing profiles are likewise altered, with the largest differences in failing hearts. 73 In humans, Kong et al 74 were the first to use a genome-wide approach to study alternative splicing changes in the diseased heart. The splicing profile of diseased and control hearts differed extensively, and subsequently, the authors were able to correctly assign samples to control or disease based solely on the splicing profile.…”
Section: Alternative Splicing In Diseasementioning
confidence: 99%
“…72 In hypertrophied and failing mouse hearts, alternative splicing profiles are likewise altered, with the largest differences in failing hearts. 73 In humans, Kong et al 74 were the first to use a genome-wide approach to study alternative splicing changes in the diseased heart. The splicing profile of diseased and control hearts differed extensively, and subsequently, the authors were able to correctly assign samples to control or disease based solely on the splicing profile.…”
Section: Alternative Splicing In Diseasementioning
confidence: 99%
“…RNA sequencing of the myocardium has revealed specific transcriptome profiles for coding and noncoding transcripts that distinguish the stages of the failing heart. 65 Recent studies have identified more than 1300 previously unannotated exons with altered expression levels in animal models of heart failure. 65 Among these, almost 682 exons displayed Figure 1.…”
Section: Novel Ncrnas In the Heartmentioning
confidence: 99%
“…65 Recent studies have identified more than 1300 previously unannotated exons with altered expression levels in animal models of heart failure. 65 Among these, almost 682 exons displayed Figure 1. interplay of chromatin modifications and non-coding RNAs regulate MHC genes in the heart.…”
Section: Novel Ncrnas In the Heartmentioning
confidence: 99%
“…Therefore, to generate a comprehensive expression profile for each exon, it is essential to perform the RNA-seq at sufficient depth. One major advantage of RNA-seq over micro-arrays is the possibility to identify novel, un-annotated exons or transcripts (Daines et al, 2011;Lee et al, 2011;Concha et al, 2012). In a recent study, we have developed two bioinformatic tools, guided transcriptome reconstruction and de novo reconstruction.…”
Section: Experimental Approaches For Total Cardiac Transcriptome Analmentioning
confidence: 99%
“…In a recent study, we have developed two bioinformatic tools, guided transcriptome reconstruction and de novo reconstruction. These tools allow detection of novel exons in known genes and novel transcript clusters (NTCs) (Lee et al, 2011).…”
Section: Experimental Approaches For Total Cardiac Transcriptome Analmentioning
confidence: 99%